2021
DOI: 10.7759/cureus.16655
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Viral Load With the Clinical and Biochemical Profiles of COVID-19 Patients

Abstract: Background/objectiveCoronavirus infectious disease (COVID-19) is a novel disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-COV-2). Some studies have shown that disease severity according to clinical and biochemical parameters are in direct relation to viral load while others have found no direct correlation. In this study, the COVID-19 cycle threshold (Ct) value, which is taken as a direct indicator of the viral load, has been correlated with the biochemical and clinical parameters in COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…Notably, 2 participants died in the 500-mg IM group vs no deaths in the 500-mg IV group. The increased rate of progression in the 250-mg IM group as compared with either of the 500-mg groups cannot be explained by differences in viral load, as AUC d1-8 values were similar across groups, consistent with findings that upper airway viral load is not an optimal biomarker for efficacy of SARS-CoV-2 treatments [ 1 , 25 , 26 ]. However, an exposure-response analysis suggested that serum concentrations on day 5 and day 8 were significant predictors of response.…”
Section: Discussionsupporting
confidence: 77%
“…Notably, 2 participants died in the 500-mg IM group vs no deaths in the 500-mg IV group. The increased rate of progression in the 250-mg IM group as compared with either of the 500-mg groups cannot be explained by differences in viral load, as AUC d1-8 values were similar across groups, consistent with findings that upper airway viral load is not an optimal biomarker for efficacy of SARS-CoV-2 treatments [ 1 , 25 , 26 ]. However, an exposure-response analysis suggested that serum concentrations on day 5 and day 8 were significant predictors of response.…”
Section: Discussionsupporting
confidence: 77%
“…It is unknown whether the observed difference in deaths was due to chance or due to some other factor. Furthermore, the increased rate of progression in the 250-mg IM group compared with either of the 500-mg groups cannot be explained by differences in viral load, because the AUC d1-8 values were similar across the groups, consistent with findings that upper airway viral load is not an optimal biomarker for efficacy of SARS-CoV-2 treatments [1,20,21]. However, an exposure response analysis suggested that serum concentrations on day 5 and day 8 were significant predictors of response.…”
Section: Discussionsupporting
confidence: 71%
“…The World Health Organization (WHO) clearly stated that the Ct is inversely proportional to the viral load, which is also supported by our findings and other studies in the literature. And it’s also advised that another sample should be taken if the test results do not match the symptoms along with a new PCR [ 7 ]. Ciotti et al, tested 50 NPS, and concluded that the sensitivity of rapid antigen test was 30.77% and had 100% specificity, never the less, it was a significantly lower result than the sensitivity claimed by the manufacturer, this was explained by low Ct values, thus it is advised by WHO to use RAT with a sensitivity ≥80% and specificity ≥97% [ 8 ].…”
Section: Discussionmentioning
confidence: 99%